2002
DOI: 10.4049/jimmunol.169.12.6856
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisAntigens Induce the Differentiation of Dendritic Cells from Bone Marrow

Abstract: We show in this study that incubation of freshly isolated bone marrow cells with Mycobacterium tuberculosis (M. tb) secretory Ag (MTSA), in the absence of any growth or differentiation-inducing factor, differentiates them into dendritic cell (DC)-like APCs. These DCs expressed moderate to high levels of various markers typical of DCs. These included T cell costimulatory molecules CD80, CD86, CD40, and CD54 and high levels of surface MHC class I and II on CD11c+ cells. The levels and the kinetics of up-regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 48 publications
(50 reference statements)
4
61
0
1
Order By: Relevance
“…We have shown that MTSA and many other secretory Ags activate DCs by inducing their differentiation and maturation (reviewed in Refs. [13][14][15]. However, a challenge of these DCs with either M. tuberculosis cell extract (CE) (16) or live M. bovis BCG (our unpublished data) down-regulates primary and recall Th1 responses.…”
Section: Impaired Generation Of Reactive Oxygen Species During Differmentioning
confidence: 99%
“…We have shown that MTSA and many other secretory Ags activate DCs by inducing their differentiation and maturation (reviewed in Refs. [13][14][15]. However, a challenge of these DCs with either M. tuberculosis cell extract (CE) (16) or live M. bovis BCG (our unpublished data) down-regulates primary and recall Th1 responses.…”
Section: Impaired Generation Of Reactive Oxygen Species During Differmentioning
confidence: 99%
“…For measuring antigen-specific T cell responses, BALB/c mice were immunized subcutaneously at the base of tail with MTSA (50 g/mouse) in incomplete Freund's adjuvant for 7 days as described previously [20]. Inguinal lymph nodes from these mice were removed, and T cells were enriched as described above.…”
Section: Syngeneic T Cell Stimulationmentioning
confidence: 99%
“…When required, these BM-derived DCs (hereafter called BMDCs) were matured with 20 g/ml MTSA or 20 ng/ml TNF-␣ [21]. For up-regulating CD86, cytokine-or antigen-activated DCs were stimulated with 50 g/ml purified anti-CD80 for 24 h. Cells at the end of incubation in all sets were analyzed for the levels of surface molecules by flow cytometry as described before [20] or cocultured with naïve, allogeneic or antigen-primed, syngeneic T cells as described below. All flow cytometric analyses were performed on CD11c ϩ -gated cells.…”
Section: Enrichment Of DC Precursors From Bone Marrow (Bm) and Generamentioning
confidence: 99%
See 2 more Smart Citations